The different extent of privatisation proceeds in EU countries: A preliminary explanation using a public choice approach - Ansgar Belke; Frank Baumgärtner; Friedrich G. Schneider; Ralph Setzer (Johannes Kepler University of Linz, Department of Economics, 2006)
This paper empirically investigates the differences in the motives of raising privatisation proceeds for a panel of EU countries from 1990 to 2000. More specifically, we test whether privatisations can be mainly interpreted (a) as ingredients of a larger reform package of economic liberalisation in formerly overregulated economies, (b) as a reaction to an increasing macroeconomic problem pressure and (c) as a means to foster growth and increase tax income and relax the fiscal stance with an eye on the demands by integration of economic and financial markets. Whereas we are able to corroborate claim (a) only partly, we gain consistent evidence in favour of claims (b) and (c).
Keywords: H42; E62; L33; 330; European Union; panel analysis; partisan theory; privatisation proceeds; state-owned enterprises; Privatisierung; Public Choice; Interessenpolitik; Schätzung; EU-Staaten